Problem Solving of Digital Marketing with Design Thinking Model - Mahajan, Vishal; Aithal; Mahajan, Shailly (Ushus Journal of Business Management, 2022)
Design thinking is the most common way of taking care of an issue for significant reasons. For taking care of the genuine issue first, the cause is essential. With the assistance of design thinking, problematic issues can be settled by addressing the main cause. Ordinarily, five stages have been utilized to tackle the issue in design thinking example, empathy, ideate, model and test. Yet, in this paper, we have used a configuration design thinking model for tracking down the problem of digital marketing. Fostering a design thinking model for taking care of a supportable computerized promoting issue. It very well may be utilized by the organizations likewise for tackling their fundamental digital marketing problems. Configuration of design thinking model gives the sensible answers for the digital marketing problems and furthermore centers around the development which can be applied while finding the underlying driver of the issue and recognizing the right arrangements with models that can be involved by the clients for their critical thinking and give various perspectives for seeing the issue. Another idea of digital marketing problem design thinking model has been created in this composition which will additionally help the community with the critical thinking process.